2015
DOI: 10.1103/physrevd.92.095008
|View full text |Cite
|
Sign up to set email alerts
|

Higgs boson decays intoγγandZγin the MSSM and theBLsupersymmetric SM

Abstract: We calculate Higgs decay rates into γγ and Zγ in the Minimal Supersymmetric Standard Model (MSSM) and (B-L) Supersymmetric Standard Model (BLSSM) by allowing for contributions from light staus and charginos. We show that sizable departures are possible from the SM predictions for the 125 GeV state and that they are testable during run 2 at the Large Hadron Collider. Furthermore, we illustrate how a second light scalar Higgs signal in either or both these decay modes can be accessed at the CERN machine rather p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…where all PV functions having divergence completely disappeared, and therefore d = 4. We would like to emphasize now that formula (14) is written in terms of PV functions which are contained in LoopTools and hence it can be easily evaluated numerically. Moreover, analytic expressions for the relevant PV functions have been constructed [10,48], that is enough to implement our results in existing numerical programs or to write a new stand-alone code.…”
Section: Total Contribution From Diagrams With Pure Gauge Boson Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…where all PV functions having divergence completely disappeared, and therefore d = 4. We would like to emphasize now that formula (14) is written in terms of PV functions which are contained in LoopTools and hence it can be easily evaluated numerically. Moreover, analytic expressions for the relevant PV functions have been constructed [10,48], that is enough to implement our results in existing numerical programs or to write a new stand-alone code.…”
Section: Total Contribution From Diagrams With Pure Gauge Boson Mediamentioning
confidence: 99%
“…Meanwhile, another loopinduced coupling h Zγ related to the decay h → Z γ has not been measured yet even so that the predicted decay rate is of the same order as the one of h → γ γ in the SM case [5]. The partial decay width h → Z γ was calculated within the SM framework and its supersymmetric extension [6][7][8][9][10][11][12][13][14]. From the experimental side, this decay channel is now been searched at the LHC by both CMS and ATLAS collaboraa e-mail: lthue@iop.vast.ac.vn b e-mail: arbuzov@theor.jinr.ru c e-mail: tthong@agu.edu.vn d e-mail: thanhphong@ctu.edu.vn e e-mail: dangtrungsi@cantho.edu.vn f e-mail: hoangngoclong@tdtu.edu.vn e Corresponding author tions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Wherever a Z is present in the MSSM, a Z ′ can also contribute. Furthermore, for each of the neutral MSSM Higgs states, h, H and A, there corresponds in the BLSSM a primed version, h ′ , H ′ and A ′ , wherein the h ′ can have a mass similar to the h one (i.e., just above 125 GeV) while the other two states are generally much heavier [10,[20][21][22], most notably in its inverse seesaw version [9]. Hence, the potential to increase the sensitivity of experimental analyses is twofold.…”
Section: Mono-higgs As a Final Statementioning
confidence: 99%
“…1. Before closing, we should also mention that the h → γγ enhancement found in the BLSSM may be mirrored in the γZ decay channel [15] for which, at present, there exists some constraints, albeit not as severe as in the γγ case. Doubtless, if the second peak is real, explanations for it can be found in other SUSY models than just the BLSSM.…”
mentioning
confidence: 99%
“…[14] (see also [15]), wherein, motivated by a ∼ 2.9σ excess recorded by the CMS experiment at the LHC around a mass of order ∼ 140 GeV in ZZ * → 4l and γγ samples, is was shown that a double Higgs peak structure can be generated in the BLSSM, with CP-even Higgs boson masses at ∼ 125 and ∼ 140 GeV, a possibility instead precluded to the MSSM. Before proceeding in this respect, though, two remarks are in order: firstly, ifg = 0, the coupling of the BLSSM lightest Higgs state, h , with the SM particles will be significantly suppressed (≤ 10 −5 relative to the SM strength), so that, in order to account for possible h signals at the LHC, this parameter ought to be sizable; secondly, in both cases of vanishing and non-vanishingg, one may fine-tune the parameters and get a light m A , which leads to a MSSM-like CP-even Higgs state, H, with m H ∼ 140 GeV.…”
mentioning
confidence: 99%